Pengaruh Kualitas Produk, Harga, Dan Lokasi Terhadap Keputusan Pembelian Mie Gacoan (Studi Pada Konsumen Mie Gacoan Di Kota Malang) - Ningtyas, Defi Fironika Ayu; Salim, Muhammad Agus; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to identify the influence of product quality, price and location on purchasing decisions on consumers of Mie Gacoan in Malang. The sample used in this study uses the maholtra formula by multiplying the number of indicators by 5, so that the number of samples taken is 75 respondents, the technique used is using non-probability sampling and using the purposive sampling method. The population used in this study is consumers who have made purchases at Mie Gacoan. The results of this study show that product quality, price and location have an impact on consumer purchase decisions, and product quality has a significant impact on purchase decisions, but price and location do not have a significant influence on purchase decisions. Keywords: Product Quality, Price and Location